Похід гетьмана Богдана Хмельницького та калги-султана Крим-Гірея до Молдавської землі в 1650 р. і його вплив на ситуацію в північних волостях країни - Чучко, Михайло Костянтинович; Chuchko, Mykhailo (Щорічник Чернівецького обласного краєзнавчого музею / відп. ред. О. В. Ротар. Чернівці : Друк Арт, 2024. Вип. 9 (2024). С. 212-227, 2024)
The change in the international situation in Eastern and South-Eastern Europe after the beginning of the War of Liberation in Ukraine in the middle of the 17th century did not bypass all the neighboring Danube voivodeships, which were in vassal dependence on the Porte, but most of all affected Moldavia, neighboring the Polish-Lithuanian state. The unfriendly actions of the voivode of Moldavia Vasile Lupu caused a hostile attitude towards him on the part of the hetman of the Zaporozhian Army B. Khmelnytsky and the Crimean Khan. Taking advantage of the desire of the ruler of Crimea to repay the voivode for the incident near Bretulen, the Cossack hetman, preventing a campaign against Moscow, which was unprofitable for him, together with the Horde, redirected the military activity of the ruler of Crimea and his brother - the Kalga Sultan, towards accessible and rich Moldavia. A surprise attack in September 1650 by the Tatar and Cossack army, accompanied by the devastation of the territory of the Moldavian land from the Dniester to the mountains, in particular the northern volosts of Khotyn, Chernivtsi and Suchavsk were devastated, forced the voivode to enter into negotiations, the result of which was the payment of a significant amount of ransom to the Tatars and the establishment of allied relations with Hetman B. Khmelnytsky, which were to be secured by a matrimonial alliance between the owner's daughter Ruxandra and the Hetman's son Timofey.
The campaign of Hetman Bohdan Khmelnytsky and Kalga Sultan Crimea-Girey to the Moldavian land in 1650 and its impact on the situation in the northern volosts of the country
Похід гетьмана Богдана Хмельницького та калги-султана Крим-Гірея до Молдавської землі в 1650 р. і його вплив на ситуацію в північних волостях країни
Щорічник Чернівецького обласного краєзнавчого музею / відп. ред. О. В. Ротар. Чернівці : Друк Арт, 2024. Вип. 9 (2024). С. 212-227
Keywords: Молдавське князівство, воєвода Васіле Лупу, північні волості Сучава, Чернівці, Хотин, Військо Запорозьке, гетьман Богдан Хмельницький, Кримське ханство, калга-султан Крим-Гірей, воєнний похід, козака, татари, молдавани; Principality of Moldavia, Voivode Vasile Lupu, northern counties of Suceava, Chernivtsi, Khotyn. Zaporozhian Army, Hetman Bohdan Khmelnytsky, Crimean Khanate, Kalga Sultan Crimea-Girey, military campaign, Cossacks, Tatars, Moldavians